Improvement the Action Efficiency of Microwave Vacuum Tube Type GI-19B by Activation its Intersurfaces - Yassin, S.Kh.; Khdhir, B. H.; Hussein, B. H.; Abd, G. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research an improvement of the efficiency of vacuum microwave tube type Gl-19B had been done by activation of internal surfaces using two specific procedures which can qualify the tubes to be reused again. The first method was the reevacuuated and heating treatment. The second method wa:s the glow discharge method which used ro clean the electrodes and improve the vacuum to about!oÂ·8 mbar. In order to study the using of both processes together, Copper samples heated in vacuwn chamber first and then used the glow discharge technique, it was found that the lowered resistance and less roughness of the surface of the copper sample after the removal of the oxide and the carbon materials from the surface of copper sample.